Intermetallic NixMy (M = Ga and Sn) Nanocrystals: A Non‐precious Metal Catalyst for Semi‐Hydrogenation of Alkynes. Issue 23 (13th April 2016) - Liu, Yuxi; Liu, Xiangwen; Feng, Quanchen; He, Dongsheng; Zhang, Libo; Lian, Chao; Shen, Rongan; Zhao, Guofeng; Ji, Yongjun; Wang, Dingsheng; Zhou, Gang; Li, Yadong
Abstract : Intermetallic Ni x My ( M = Ga and Sn) nanocrystals with uniform particle size and controlled composition are successfully synthesized via a solution‐based co‐reduction strategy. The as‐obtained nanocrystals are crystalline and structurally ordered. The active‐site isolation and modified electronic structure are responsible for the excellent catalytic performance for alkyne semi‐hydrogenation of the as‐obtained non‐precious catalysts.